2020
DOI: 10.1001/jamanetworkopen.2019.20973
|View full text |Cite
|
Sign up to set email alerts
|

Association of Tuberculosis With Household Catastrophic Expenditure in South India

Abstract: IMPORTANCE The high household costs associated with tuberculosis (TB) diagnosis and treatment can create barriers to access and adherence, highlighting the urgency of achieving the World Health Organization's End TB Strategy target that no TB-affected households should face catastrophic costs by 2020.OBJECTIVE To estimate the occurrence of catastrophic costs associated with TB diagnosis and treatment and to identify socioeconomic indicators associated with catastrophic costs in a setting where TB control strat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
33
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(42 citation statements)
references
References 18 publications
5
33
2
Order By: Relevance
“…The median costs reported in the present study were lower than those reported in most other studies from India [9,10,12,13,16,17,22,23]. The discrepancy might be because the current study estimated the costs among drug-susceptible pulmonary TB patients, whereas the published literature is inclusive of cost estimates on drug-resistant and extra-pulmonary TB patients.…”
Section: Discussioncontrasting
confidence: 86%
See 2 more Smart Citations
“…The median costs reported in the present study were lower than those reported in most other studies from India [9,10,12,13,16,17,22,23]. The discrepancy might be because the current study estimated the costs among drug-susceptible pulmonary TB patients, whereas the published literature is inclusive of cost estimates on drug-resistant and extra-pulmonary TB patients.…”
Section: Discussioncontrasting
confidence: 86%
“…Studies in India reported the percentage of catastrophic costs among drug-susceptible TB patients to be between 7 and 32% [9][10][11][12]. The average costs incurred by drug-susceptible TB patients treated in government health facilities are approximately USD 179, [9,10] whereas costs incurred by TB patients accessing care in all types of health facilities range from USD 20 to 224 [13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study examining the catastrophic total costs due to TB among patients treated in the NTCP network under a designated hospital service model, we found that more than one-third of patients and their households who were diagnosed and treated in designated hospitals face financial disasters due to TB, especially those with MDR. The incidence of catastrophic costs in this survey is lower than those of Ghana [15] and Vietnam [16], and is similar to the results of studies in Indonesia [17], Peru [18], and southern India [19]. We identified several independent factors associated with catastrophic total costs in this study, these factors could have influenced healthcare costs through different mechanisms.…”
Section: Discussionsupporting
confidence: 84%
“…These findings highlighted that in addition to reducing the direct costs of TB care for patients, especially those with MDR and severe adverse drug reactions [15], other financial protection measures such as compensation for income losses were needed to prevent low-income households from incurring catastrophic costs following TB diagnosis [2,14,16]. Consistent with studies in other countries [17][18][19], there was an obviously negative correlation between the household's economic status and the occurrence of catastrophic total costs, that is, financially vulnerable households were more likely to suffer catastrophic costs. This prompted us to think about the drawbacks of the balanced subsidy policy.…”
Section: Discussionsupporting
confidence: 70%